2008
DOI: 10.1585/pfr.3.s1086
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Iron Density at the Plasma Center Using Radial Profile of FeKα Lines in LHD

Abstract: Radial profiles of K α X-ray spectra of metallic impurities have been measured using an assembly of soft X-ray pulse-height analyzers in Large Helical Device. The assembly is quipped with a radial scanning system, which gives us detailed profile information, especially in long pulse discharges. The local emissivity profiles of the Fe-K α X-ray spectra have been quantitatively obtained by an Abel inversion technique. The density profile of the iron impurity in each charge state is analyzed using the energy shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The energy resolution of E/ΔE is estimated from the x-ray emissivity in LHD. The emissivity integrated between 3.0 and 10 keV is 1.5 × 10 18 photons/m 3 /s in the case of typical NBI plasmas of LHD [3]. This fact means in the case of the configuration that the incident intensity is 2.5 × 10 6 photons/s/pixel.…”
Section: Design Of Assembly Of Pin-hole Camera In Lhdmentioning
confidence: 89%
See 1 more Smart Citation
“…The energy resolution of E/ΔE is estimated from the x-ray emissivity in LHD. The emissivity integrated between 3.0 and 10 keV is 1.5 × 10 18 photons/m 3 /s in the case of typical NBI plasmas of LHD [3]. This fact means in the case of the configuration that the incident intensity is 2.5 × 10 6 photons/s/pixel.…”
Section: Design Of Assembly Of Pin-hole Camera In Lhdmentioning
confidence: 89%
“…The x-ray spectroscopy for plasma physics is important to study the behaviors of electrons and impurities such as argon and transition metals [1,2]. Recently, the local emissivities of impurity line and the bremssstrahlung emitted from electrons have been estimated from the timeresolved profiles of x-ray spectra [3]. Especially, it is confirmed that the energy and spatial distributions of the electrons is non-thermal in ECH plasma [4].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be noted that the edge plasma diagnostics using polarization spectroscopy [23] and magnetic dipole forbidden transition [24,25] have been newly tried in the visible range. The charge state distribution of iron has been studied using Kα X-ray lines for core impurity transport [26,27] . Spectroscopy on ablation cloud of the impurity pellet has also been started as part of the particle diffusion study [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Iron most likely needs to be in the plasma state. Then it contains considerably more free electrons than in a liquid state [38].…”
Section: Moon's Internal Heatmentioning
confidence: 99%